Determining and Interpreting the Key Financial Indicators in an Audiovisual Organization - Bogdan Cosmin GOMOI (CECCAR Business Review)

(untitled)
The audiovisual sector represents a field of activity that has experienced extraordinary dynamics over the past decades, reflecting itself in increasing individual diversity, as well as increasing competition within the field. The specific features of this sector inevitably influences financial information, with the most relevant being the summarized information included in financial reporting. This summarized financial information aim at the financial position, financial performance, and their variation. By capitalizing on this information, various indicators can be determined and interpreted, some derived from the financial position, others from the performance, and others from both. Thus, while structural, solvency, and financial balance indicators describe the financial position, and profitability indicators describe performance, profitability and turnover indicators incur both financial position and financial performance. This paper focuses on determining and interpreting these indicators in the case of a leader in the Romanian audiovisual sector, namely Pro TV SRL, highlighting the specific aspects for the last decade (2014-2023).